Web-Based Personnel Information System Development At Trisakti Pharmacy - Fariz, Muhammad; Syaifudin; Salim, Agus (Intelmatics, 2025)
In this day and age, technological developments are developing rapidly, in making it easier for workers to do many things. One of them is in the management of the staffing system which is very much needed for the Pharmacy business sector which still uses the system manually in recording staffing at the pharmacy, so the author aims to develop web-based staffing information system website at the Trisakti pharmacy, the author uses the waterfall method as an analysis method and for system design the author uses the System Development Life Cycle (SDLC). As well as the method for making the application using tools such as Sublime Text, MySQL, XAMPP as a database with the PHP and HTML programming languages. The development of the staffing system in this system aims to provide convenience for the Trisakti Pharmacy in managing attendance data, applying for leave, staffing, employee salaries and printing staffing reports and evaluating employee performance.